The Rambu Solo’ Tradition from a Qualitative Perspective: Social Meaning and the Dynamics of Implementation Costs - Jemi Pabisangan Tahirs (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The Rambu Solo’ tradition is a Torajan funeral ritual that embodies profound spiritual, social, and economic significance. Conducted over several days, the ceremony involves a series of traditional rituals, offerings, and cultural performances, reflecting respect for the deceased while strengthening family and communal ties. Roles in the ceremony are distributed according to social status and kinship, highlighting collective responsibility and solidarity. The implementation process requires careful coordination, resource management, and adherence to adat calendars maintained by community elders. This tradition has notable economic implications, as the costs—primarily for sacrificial buffaloes—can exceed IDR 100 million, posing financial challenges, especially for urban families. These costs are mitigated through collective funding systems such as communal contributions, adat savings groups, and support from the Torajan diaspora. Despite modernization pressures, the tradition adapts by simplifying rituals, integrating digital documentation, and educating younger generations, preserving core values while accommodating contemporary realities. Qualitative field data, supported by descriptive statistics from 40 respondents including community leaders, family members, and ritual participants, reveal that Rambu Solo’ maintains its symbolic and social relevance. The practice continues to foster spiritual devotion, social cohesion, and cultural identity while demonstrating adaptive strategies that balance economic constraints with tradition. The Rambu Solo’ ritual thus exemplifies the resilience and dynamic nature of Torajan culture in the face of modern social and economic changes.